Association between e-selectin and AMPD-1 gene polymorphisms and essential hypertension in selected Malaysian subjects - Nemati, Reza (2013)
Essential hypertension (EH) is one the most common multifactorial disorders associated with significant risk for cardiovascular and renal comorbidity. Prevalence of hypertension is increasing annually in Malaysia. Studies indicate that the high prevalence of hypertension in this population is most common among males. Unfortunately, despite the high frequency of hypertension and its dread effects, few studies have been conducted on the Malaysian population. In contrast to the high rate of hypertension in Malaysia, hypertension prevalence is decreasing significantly in developed countries. A few studies have been carried out to explore primary hypertension in more detail among the Malaysian population. It is indicated that 30% to 50% of the etiologic factors related to the development of essential hypertension are genetically-rooted. The aim of this current study was to determine the association of E-selectin and Adenosine Monophosphate Deaminase1 (AMPD1) genes polymorphism with essential hypertension among Malaysian subjects. The two genes were selected based on their function in the development of hypertension. As for the E-selectin, its functions are associated with pro-inflammatory effect, whereas for AMPD1, its influence on metabolism may be related in the etiology of hypertension. Two hundred hypertensive and 200 normotensive individuals were recruited in this study, and their DNA were analyzed in order to determine the polymorphism of E-selectin and AMPD1 genes. The PCR-RFLP method was used in this research. After extracting DNA using an available commercial DNA extraction kit, the DNA was incubated with the restriction enzyme to be cut into different fragments. Subsequently, post stain was carried out. To visualize DNA, the UV image capturing system was carried out to identify three forms of DNA pattern. There were significant associations observed for the selected gene polymorphisms and hypertension, namely, the S128R polymorphism of E-selectin (chi-squared, p<0.05) ; regarding AMPD1, for C34T, G468T and C143T (chi-squared, p<0.05). It is indicated that for the Eselectin S128R polymorphism, the R allele has a potent effect on essential hypertension (odds ratio 6.6, 95% CI 3.46-9.89); in addition, for the C34T, T allele carriers are 9.49 times more at risk of hypertension (odds ratio 9.49, 95% CI 5.6-16.02) . Furthermore, C143T subjects who are T carriers are 3.85 times more at risk of primary hypertension (odds ratio 3.85, 95% CI 1.86-6.70), while for G468T there was no difference observed with respect to both alleles (odds ratio 1, 95% CI, 0.65-1.52). Also, there was a significant association observed between S128R polymorphism and increased level of SBP. Furthermore, in terms of SBP and DBP, there was a significant association observed among C34T genotypes. In this study, there was not significant relationship between smoking and gender based on different genotypes. In conclusion, this study shows the significant potential of Eselectin and AMPD1 on the development of essential hypertension. These genes may be considered as a risk factor for subjects who are predisposed to hypertension. However, further studies which involve more samples and different populations need to be carried out.